GE_GERICHTE A/2739/2024 vom 3. September 2024 - GE Cour de justice (2024)
PROLONGATION;MESURE DE CONTRAINTE(DROIT DES ÉTRANGERS);DÉTENTION AUX FINS D'EXPULSION | LEI.75.al1.leth; LEI.76.al1.letb.ch3; LEI.79